2009
DOI: 10.1590/s0103-50532009000100029
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of a tetrahydrofuran lignan by the endophytic fungus Phomopsis Sp.

Abstract: A biotransformação da lignana tetraidrofurânica, (-)-grandisina, pelo fungo endofítico Phomopsis sp, obtido de Viguiera arenaria, conduziu à formação de um novo metabólito caracterizado como 3,4-dimetil-2-(4'-hidróxi-3',5'-dimetóxifenil)-5-metóxi-tetraidrofurano. O metabólito foi analisado contra o parasita Trypanosoma cruzi, o agente causador da doença de Chagas, e mostrou uma atividade tripanocida (IC 50 9,8 µmol L -1 ) similar ao precursor natural (IC 50 3,7 µmol L -1 ).The biotrasformation of the tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
0
27
0
4
Order By: Relevance
“…7, 11). The metabolite had trypanocidal activity (IC 50 9.8 μmol/mL) similar to the natural precursor (IC 50 3.7 μmol/mL) (Verza et al, 2009). Fig.…”
Section: Bioactive Compounds Against Neglected Diseasesmentioning
confidence: 65%
“…7, 11). The metabolite had trypanocidal activity (IC 50 9.8 μmol/mL) similar to the natural precursor (IC 50 3.7 μmol/mL) (Verza et al, 2009). Fig.…”
Section: Bioactive Compounds Against Neglected Diseasesmentioning
confidence: 65%
“…The residue purified by column chromatography on silica gel using hexane/ethyl acetate 8:2 as eluent. General procedure for the preparation of triazole derivatives (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) To a solution of terminal acetylenes 25a-d (2 mmol, 1.0 equiv) and azides 27a-d (2 mmol, 1.0 equiv) in dichloromethane (2 mL) and water (2 mL), were added CuSO 4 .5H 2 O pentahydrate (0.128 mmol, 0.064 equiv) and sodium ascorbate (0.352 mmol, 0.176 equiv). The reaction mixture was stirred for 24 h. Then was added a saturated solution of NH 4 Cl (30 mL) and the product was extracted with dichloromethane (3 × 20 mL).…”
Section: General Remarksmentioning
confidence: 99%
“…10,12,13 Among natural products, our research group has focused on the tetrahydrofuran neolignans, a class that exhibits a great number of biological activities including antibacterial, antifungal, antitumor, and anti-inflammatory. [14][15][16][17][18][19][20][21][22][23] The neolignans veraguensin 1, grandisin 2, and machilin G 3 ( Figure 1) have shown antitrypanosomal and antileishmanial activities. [14][15][16][17][18][19][20][21][22][23] Studies on the antitrypanosomal activity of compounds 1-3 found maximum inhibitory concentration (IC 50 ) values of 2.3, 3.7 and 2.2 µM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi have also drawn attention as potential producers of many products, including industrially interesting enzymes. Endophytic fungi exhibit a complex web of interactions with the host plants and have been extensively studied over the last several years as prolific sources of new bioactive natural products, including new enzymes with interesting properties for industrial application (Verza et al 2009;Borges et al 2009;Fernandes et al 2009). However, very few endophytic fungi have been reported as producers of lipase.…”
Section: Lipasesmentioning
confidence: 99%